2008
DOI: 10.1111/j.1600-0447.2008.01252.x
|View full text |Cite
|
Sign up to set email alerts
|

Validity of ‘post‐traumatic stress disorder with secondary psychotic features’: a review of the evidence

Abstract: There is currently not yet full support for PTSD-SP as a nosological entity. However, the delineation of PTSD-SP from other psychiatric syndromes is notable and biological studies seem to support the validity as a separate diagnostic entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
1
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(106 citation statements)
references
References 44 publications
(59 reference statements)
6
92
1
7
Order By: Relevance
“…Although MDD is signifi cantly associated with the Met allele of BDNF in male subjects (Verhagen et al 2010), our results showed no signifi cant association between the BDNF polymorphism and MDD in veterans with PTSD, compared to veterans with PTSD without any comorbidity. These data are in line with the evidence that particular peripheral markers, such as concentrations of plasma cortisol, cerebrospinal fl uid corticotrophin releasing hormone, platelet serotonin, and activity of platelet monoamine oxidase and plasma dopamine beta hydroxylase, are higher in psychotic compared to non-psychotic PTSD (Sautter et al 2003;Hamner et al 2004;Pivac et al 2006Pivac et al , 2007Braakman et al 2008Braakman et al , 2009Shevlin et al 2010). We might speculate that early intervention for this more severe subtype of PTSD, complicated with psychotic features, would be treatment with atypical antypsychotics as monotherapy, or as add-on therapy with antidepressants.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Although MDD is signifi cantly associated with the Met allele of BDNF in male subjects (Verhagen et al 2010), our results showed no signifi cant association between the BDNF polymorphism and MDD in veterans with PTSD, compared to veterans with PTSD without any comorbidity. These data are in line with the evidence that particular peripheral markers, such as concentrations of plasma cortisol, cerebrospinal fl uid corticotrophin releasing hormone, platelet serotonin, and activity of platelet monoamine oxidase and plasma dopamine beta hydroxylase, are higher in psychotic compared to non-psychotic PTSD (Sautter et al 2003;Hamner et al 2004;Pivac et al 2006Pivac et al , 2007Braakman et al 2008Braakman et al , 2009Shevlin et al 2010). We might speculate that early intervention for this more severe subtype of PTSD, complicated with psychotic features, would be treatment with atypical antypsychotics as monotherapy, or as add-on therapy with antidepressants.…”
Section: Discussionsupporting
confidence: 74%
“…Psychotic symptoms, such as auditory and visual hallucinations, delusional thinking, paranoia and violent thoughts, are often present in combat veterans with posttraumatic stress disorder (PTSD) (Sautter et al 2003;Pivac et al 2004;Kozaric-Kovacic and Pivac 2007;Braakman et al 2008Braakman et al , 2009Shevlin et al 2010). PTSD with secondary psychotic features occurs in 30 -40% of patients with combat-related PTSD (Hamner et al 2004;Kozaric-Kovacic and Borovecki 2005), has a complex clinical presentation and is often misdiagnosed and undertreated.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, dataset 4 / network 4 which stand out somewhat from the others was estimated in a population of refugees with 30% prevalence of persistent psychotic symptoms. While psychotic symptoms are not uncommon in individuals with PTSD, they might constitute a special PTSD-subtype (Braakman, Kortmann, & van den Brink, 2009). Unfortunately, the etiology of PTSD with psychotic symptoms is still poorly understood, and some lines of inquiry indicate that comorbid depression with psychotic symptoms might be responsible for this co-occurrence (Gaudiano & Zimmerman, 2010).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Such a proposition is contradicted by the finding that PTSD-AVH are phenomenologically distinct from auditory flashbacks where the person acts or feels as if the traumatic event is actually recurring (Butler et al, 1996). Furthermore, PTSD-AVH are not confined to episodes of re-experiencing, but remain present continuously as in SZ-AVH (Braakman et al, 2009).…”
Section: The Phenomenology Of Avh In Ptsd and Schizophrenia Argumentsmentioning
confidence: 99%